Neonates' responses to repeated exposure to a still face. - Emese Nagy; Karen Pilling; Rachel Watt; Attila Pal; Hajnalka Orvos (PLoS ONE)
Aim The main aims of the study were to examine whether human neonates' responses to communication disturbance modelled by the still-face paradigm were stable and whether their responses were affected by their previous experience with the still-face paradigm. Methods The still face procedure, as a laboratory model of interpersonal stress, was administered repeatedly, twice, to 84 neonates (0 to 4 day olds), with a delay of an average of 1.25 day. Results Frame-by-frame analysis of the frequency and duration of gaze, distressed face, crying, sleeping and sucking behaviours showed that the procedure was stressful to them both times, that is, the still face effect was stable after repeated administration and newborns consistently responded to such nonverbal violation of communication. They averted their gaze, showed distress and cried more during the still-face phase in both the first and the second administration. They also showed a carry-over effect in that they continued to avert their gaze and displayed increased distress and crying in the first reunion period, but their gaze behaviour changed with experience, in the second administration. While in the first administration the babies continued averting their gaze even after the stressful still-face phase was over, this carry-over effect disappeared in the second administration, and the babies significantly increased their gaze following the still-face phase. Conclusion After excluding explanations of fatigue, habituation and random effects, a self-other regulatory model is discussed as a possible explanation for this pattern.